Информационно-библиографическое обеспечение научно-технических проблем - Варнене Рeгинa (Knygotyra, 1991)
As is discovered, current state of information and bibliographical supply of cardinal scientific and technical problems is by no means satisfactory, since information centers, irrespective of their level, do not account for the whole cycle of problem solving process and, consequently, but a part of subject sections pertaining to separate problems is supplied (with information); formulation of subject requests applied by executives or managers involved in problem solutions do not coincide with subject requests obtained from all-level informtion bodies. It is possible to improve information and bibliographical supply of scientific and technical problems on the basis of problem-oriented system which is expedient to be developed in coordination center. The suggested functional structure of the system discloses the subject structure of scientific and technical problems, subject and type as well as subject structure of document resources, reflects collection of request and information holdings and also enables to observe the actual state and development of problems.